Tunable Chemical Release from Polyester Thin Film by Photocatalytic Zinc Oxide and Doped LiYF4 Upconverting Nanoparticles - Cheng, Ting (2017)
Once manufactured or implanted, polyester release kinetics tend to be fixed with little modulation possible for optimal local chemical concentrations. Here, a typical implantable polyester was fabricated into thin films (∼50 μm thick) with additives of photocatalytic ZnO nanoparticles, lanthanide-doped LiYF4 nanoparticle upconverting nanoparticles, or a combination thereof and irradiated with either 6 mW ultraviolet (365 nm) light emitting diodes or 50 mW near-infrared (980 nm) laser diodes to induce polymer photooxidation. Irradiated polyester films with the aforementioned photoadditives had enhanced release kinetics up to 30 times more than nonirradiated, neat films with extended release times of 28 days. Near-infrared, ZnO-mediated photocatalysis had the highest light on/light off ratio release kinetics of 15.4, while doped LiYF4 upconversion nanoparticles paired with ZnO nanoparticles had the highest linear R2 correlation of 0.98 with respect to duty cycle and release kinetics. Future applications of the technology will aim toward modulation of previously developed polymeric reagents/drugs for real-time, feedback-optimized release.